MEGATENDENCIES OF MODERN WORLD AND EDUCANION - Сухова, Н. М. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Philosophical analysis of megatendencies of the Modern World and the ideal of man’s intelligence in the XIX century is researched in the article.